A force balance model for a cell size‐dependent meiotic nuclear oscillation in fission yeast. (9th January 2023) - Fujita, Ikumi; Kimura, Akatsuki; Yamashita, Akira
Abstract: Fission yeast undergoes premeiotic nuclear oscillation, which is dependent on microtubules and is driven by cytoplasmic dynein. Although the molecular mechanisms have been analyzed, how a robust oscillation is generated despite the dynamic behaviors of microtubules has yet to be elucidated. Here, we show that the oscillation exhibits cell length‐dependent frequency and requires a balance between microtubule and viscous drag forces, as well as proper microtubule dynamics. Comparison of the oscillations observed in living cells with a simulation model based on microtubule dynamic instability reveals that the period of oscillation correlates with cell length. Genetic alterations that reduce cargo size suggest that the nuclear movement depends on viscous drag forces. Deletion of a gene encoding Kinesin‐8 inhibits microtubule catastrophe at the cell cortex and results in perturbation of oscillation, indicating that nuclear movement also depends on microtubule dynamic instability. Our findings link numerical parameters from the simulation model with cellular functions required for generating the oscillation and provide a basis for understanding the physical properties of microtubule‐dependent nuclear movements. Synopsis: In fission yeast, the meiotic nucleus exhibits oscillatory movement, which is driven by cytoplasmic dynein. A model that considers various microtubule properties, including pulling and pushing forces, recaptures robust nuclear oscillations. A model considering microtubule pulling and pushing forces recapitulates the premeiotic nuclear oscillation in fission yeast. Period of the spindle pole body (SPB) oscillation correlates with cell length. Speed of the SPB movement is limited by viscous drag force associated with nuclear volume. Kinesin‐8 family protein Klp6 contributes to efficient oscillation by controlling microtubule catastrophe. Abstract : In fission yeast, the meiotic nucleus exhibits oscillatory movement, which is driven by cytoplasmic dynein. A model that considers various microtubule properties, including pulling and pushing forces, recaptures robust nuclear oscillations.